THERMAL DESTRUCTION OF COALS, METAMORPHISM OF COAL SEAMS AND THEIR HAZARDOUS PROPERTIES - Brozhko, Rostyslav; Filatiev, Mykhailo; Filatieva, Elvira; Antoshchenko, Mykola; Rudniev, Yevhen (European Science, 2022)
THERMAL DESTRUCTION OF COALS, METAMORPHISM OF COAL SEAMS AND THEIR HAZARDOUS PROPERTIES